Effect of insulation location on dynamic heat-transfer characteristics of building external walls and optimization of insulation thickness - Ozel, Meral (Elsevier Science Sa, 2014)
In this study, the effect of insulation location on the heat transfer characteristics of building walls and optimization of insulation thickness are investigated numerically using an implicit finite difference method under steady periodic conditions. The investigation is carried out for a south-facing wall in the climatic conditions of Elazig, Turkey. For this purpose, insulation is placed at outside, inside and middle of the wall. Firstly, thermal characteristics such as cooling and heating transmission loads, time lag and decrement factor are determined for each insulation position. Then, the insulation thickness is optimized by using a cost analysis over a building lifetime of 20 years. Results show that insulation location has a significant effect on the yearly averaged time lag and decrement factor. However, yearly transmission loads and hence, optimum insulation thickness are not affected by insulation location. It is seen the maximum temperature swings and peak load in both summer and winter occur in the case that insulation is placed at middle of wall while wall with outside insulation gives the smallest fluctuation. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Insulation location; Heat transfer characteristics; Optimum insulation thickness